Secondhand smoke exposure and risk following the Irish smoking ban: an assessment of salivary cotinine concentrations in hotel workers and air nicotine levels in bars - Mulcahy, M (BMJ Group, 2005)
Objective: To investigate whether the Irish smoking ban has had an impact on secondhand smoke (SHS) exposures for hospitality workers. Design, setting, and participants: Before and after the smoking ban a cohort of workers (n = 35) from a sample of city hotels (n = 15) were tested for saliva cotinine concentrations and completed questionnaires. Additionally, a random sample (n = 20) of city centre bars stratified by size (range 400–5000 square feet), were tested for air nicotine concentrations using passive samplers before and after the ban. Main outcome measures: Salivary cotinine concentrations (ng/ml), duration of self reported exposures to secondhand smoke, air nicotine (µg/cubic metre). Results: Cotinine concentrations reduced by 69%, from 1.6 ng/ml to 0.5 ng/ml median (SD 1.29; p < 0.005). Overall 74% of subjects experienced decreases (range 16–99%), with 60% showing a halving of exposure levels at follow up. Self reported exposure to SHS at work showed a significant reduction from a median 30 hours a week to zero (p < 0.001). There was an 83% reduction in air nicotine concentrations from median 35.5 µg/m(3) to 5.95 µg/m(3) (p < 0.001). At baseline, three bars (16%) were below the 6.8 µg/m(3) air nicotine significant risk level for lung cancer alone; at follow up this increased to 10 (53%). Conclusions: Passive smoking and associated risks were significantly reduced but not totally eliminated. Exposure to SHS is still possible for those working where smoking is still allowed and those working where smoke may migrate from outdoor areas. Further research is required to assess the true extent and magnitude of these exposures.